2017
DOI: 10.18632/oncotarget.17770
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p38-βTrCP-Tristetraprolin-TNFα axis in radiation pneumonitis

Abstract: Early release of tumor necrosis factor-alpha (TNF-α) during radiotherapy of thoracic cancers plays an important role in radiation pneumonitis, whose inhibition may provide lung radioprotection. We previously reported radiation inactivates Tristetraprolin (TTP), a negative regulator of TNF-α synthesis, which correlated with increased TNF-α release. However, the molecular events involved in radiation-induced TTP inactivation remain unclear. To determine if eliminating Ttp in mice resulted in a phenotypic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It has been shown that TTP inhibits inflammatory cytokine production by destabilizing target mRNAs 14,15 while HuR functions oppositely to stabilize cytokine (see figure on previous page) Fig. 5 GSK-3β modulated the expression and function of TTP and HuR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that TTP inhibits inflammatory cytokine production by destabilizing target mRNAs 14,15 while HuR functions oppositely to stabilize cytokine (see figure on previous page) Fig. 5 GSK-3β modulated the expression and function of TTP and HuR.…”
Section: Discussionmentioning
confidence: 97%
“…Tristetraprolin binds to the AREs of mRNAs encoding multiple inflammatory cytokines and promotes their degradation 13 . For example, TTP inhibits TNF-α synthesis by destabilizing TNF-α mRNA 14,15 and it is upregulated during inflammatory responses to decrease proinflammatory gene expression 16 . We previously reported that urinary and serum levels of TTP are lower in patients with diabetes and clinical proteinuria than in healthy individuals 16 , indicating that TTP might negatively modulate DKD progression.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this would be more attractive than current second line anti-androgen treatments remains to be seen, and would probably depend on toxicity profiles and co-morbidities. On that note, p38 is well-known to regulate inflammation, and a few studies have suggested that p38 inhibition might mitigate radiation-induced gene expression associated with promotion of inflammation [ 35 , 36 , 37 ]. It would be interesting to assess whether p38 inhibition thereby could offer radioprotection of normal tissues and further widen the therapeutic window in the context of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of pro-inflammatory cells in the lung is associated with increased local expression of cytokines and chemokines post-irradiation [ 4 , 13 ]. IL-1β and TNF-α are produced by activated macrophages and are associated with airway hyper-responsiveness and pneumonitis [ 65 , 66 ]. Additionally, TNF-α expression is believed to be important for subsequent fibrosis following radiation exposure [ 13 ].…”
Section: Discussionmentioning
confidence: 99%